The Role of Business Information Systems in Strategic Decision-Making: Implications for Innovation and Market Adaptation - Fahrina Mustafa; Abu Muna Almaududi Ausat; Kraugusteeliana Kraugusteeliana (Politeknik Ganesha Medan, 2024)
Business information systems have evolved into a crucial pillar of strategic decision-making across various organizations. With the accelerating changes in the business environment driven by technological advancements and globalization, information systems play a key role in providing the data and analysis necessary to support more precise and accurate decision-making. This research utilizes a literature review with a qualitative approach, drawing data from relevant literature sources. The primary data sources include scholarly articles accessed via Google Scholar, published between 2013 and 2024. The study reveals that business information systems are vital in supporting strategic decision-making, innovation, and market adaptation. The use of systems such as ERP, CRM, and BI provides access to real-time data essential for formulating more effective business strategies, improving operational efficiency, and responding swiftly to market changes. Case studies from various companies, including Tokopedia, GoTo, and Astra International, demonstrate that optimal use of business information systems not only aids in identifying new business opportunities but also enhances the capability to innovate and adapt to evolving market dynamics.